Multi‐scenario simulation on reducing CO2 emissions from China's major manufacturing industries targeting 2060. (23rd December 2021) - Zhou, Sheng; Gu, Alun; Tong, Qing; Guo, Yuefeng; Wei, Xinyang
Abstract: CO2 emissions from industrial processes are the main components of global greenhouse gas emissions. Based on analyzing the industrial activity level, technological progress, raw material substitution, and CO2 recycling ratio from the cement, aluminum, ammonia, steel, lime, and ferroalloy industries, this paper considers three scenarios, namely, national determined contribution (NDC), carbon mitigation scenario (CMS), and deep mitigation scenario (DMS), and systematically explores the CO2 emissions from future industrial processes as well as relevant cumulative emissions, emission sources, mitigation potentials, and mitigation sources in China. The results demonstrate that CO2 emissions of the six main industrial processes can be continuously and significantly reduced in China. In the scenarios, compared with the 2020 level (1448 million metric tons of CO2 ), the CO2 emissions can be reduced by 71%, 82%, and 94%, respectively, in 2060, mainly owing to the reduction of the activity level, the adjustment of the product structure and the application of carbon capture and storage (CCS) under the DMS scenario. This paper provides several major policy implications to reduce the CO2 emissions through adjusting the industrial structure and current lifestyles, improving the durability of industrial products and the management and technical levels, increasing the substitution ratio of low‐carbon raw materials in industrial production, supporting innovative low‐carbon technologies, the establishment and operation of the carbon market and carbon pricing mechanism, and further promoting the current "leader" system of energy‐intensive industries.